2010
DOI: 10.1007/s10439-010-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Standing Posture for X-Ray Radiography: A Feasibility Study of the BalancAid with Healthy Young Subjects

Abstract: Unreliable spinal X-ray radiography measurement due to standing postural variability can be minimized by using positional supports. In this study, we introduce a balancing device, named BalancAid, to position the patients in a reproducible position during spinal X-ray radiography. This study aimed to investigate the performance of healthy young subjects’ standing posture on the BalancAid compared to standing on the ground mimicking the standard X-rays posture in producing a reproducible posture for the spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Given the high impact of a reproducible posture, several authors have provided practical recommendations for patient positioning during radiography. Dewi et al [ 34 ] suggested a balancing plate that comprises a square board with a cylindrical disk at the center point attached at the center of the bottom. This design was aimed at realizing a forced balance in the sagittal and frontal planes.…”
Section: Possible Reasons For the Failure Of The Current Sagittal Defmentioning
confidence: 99%
“…Given the high impact of a reproducible posture, several authors have provided practical recommendations for patient positioning during radiography. Dewi et al [ 34 ] suggested a balancing plate that comprises a square board with a cylindrical disk at the center point attached at the center of the bottom. This design was aimed at realizing a forced balance in the sagittal and frontal planes.…”
Section: Possible Reasons For the Failure Of The Current Sagittal Defmentioning
confidence: 99%
“…[ 3 ] It is not unheard of for patients to report that their previous chiropractor informed them their pelvis is “misaligned” or “rotated.” Various factors can influence this extremely dogmatic approach to a patient’s assessment, including alteration of patient positioning, variation in an individual’s anatomy, inter-examiner reliability, and overall image quality. [ 8 - 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of additional validation, three new CT scans were added, each paired with the corresponding two natural X-ray images of the same bone as in the CT scan; the first natural X-ray image showed the bone from the anteroposterior and the second from the mediolateral view. Using the software MeVisLab, we generated 900 artificial 2D X-ray images for each of the 29 CT scans by varying the viewing angle and radiation exposure, thus simulating the variability of conditions during clinical X-ray image acquisition 32,33 . These 26,100 images served as the dataset to train and evaluate the neural network on.…”
Section: Resultsmentioning
confidence: 99%